LB-3. Oral Tebipenem Pivoxil Hydrobromide is Non-inferior to IV Ertapenem in Complicated Urinary Tract Infection (cUTI) and Acute Pyelonephritis (AP) – Results from the Pivotal ADAPT-PO Study. (31st December 2020) - Muir, Lori A; Walpole, Susannah M; Warfel, Patricia A; Kwak, Hanna; Phelan, Anne-Marie; Moore, Gary E; Jain, Akash; Keutzer, Tim; Dane, Aaron; Dane, Aaron; Melnick, David; Talley, Angela K
Abstract: Background: Tebipenem pivoxil hydrobromide (TBP-PI-HBr) is an orally bioavailable prodrug that is rapidly converted in plasma to the carbapenem, tebipenem. Tebipenem has in vitro activity against select multidrug-resistant Gram-negative pathogens, including fluoroquinolone-resistant and extended-spectrum ß-lactamase (ESBL)-producing Enterobacterales. TBP-PI-HBr is being developed in the United States as the first oral carbapenem for treatment of cUTI and AP. Methods: ADAPT-PO was a global, double-blind, Phase 3 study to evaluate the efficacy and safety of oral TBP-PI-HBr vs. IV ertapenem in hospitalized adult patients with cUTI or AP. The primary endpoint was overall response (composite clinical cure and microbiologic eradication) at the test-of-cure (TOC) visit (Day 19 ± 2) in the micro-ITT population. Patients (N=1372) were randomized 1:1 to receive TBP-PI-HBr 600 mg PO q8h plus placebo IV q24h or ertapenem 1 g IV q24h plus oral placebo q8h for 7–10 days (or up to 14 days in patients with bacteremia). Results: Oral TBP-PI-HBr met the primary objective of non-inferiority compared with IV ertapenem with an overall response rate of 58.8% (264/449) vs. 61.6% (258/419), respectively (treatment difference -3.3%; 95% CI: -9.7, 3.2; -12.5% NI margin). Clinical cure rates at TOC were > 93% in both treatment groups. Microbiological response rates for target uropathogens were comparable across treatment groups. TBP-PI-HBr was well tolerated. Treatment-emergent adverse events (TEAEs) were observed in 25.7% TBP-PI-HBr and 25.6% ertapenem patients. Most TEAEs were mild; premature discontinuation of study drug was uncommon (< 1%). The most frequent TEAEs were diarrhea (5.0%) and headache (3.8%). No C. difficile -associated TEAEs were observed in the TBP-PI-HBr group; 3 cases occurred in the ertapenem group. Serious adverse events were infrequent (1.3% vs. 1.7%), with no deaths. Conclusion: Results from this pivotal Phase 3 study provide the first head-to-head demonstration of non-inferiority of an oral (TBP-PI-HBr) antibacterial agent to an IV (ertapenem) agent in patients with cUTI and AP, with a comparable tolerability profile. If approved in the U.S., TBP-PI-HBr would provide a new oral therapeutic option — and the first oral carbapenem — for patients with serious Gram-negative infections. Disclosures: Lori A. Muir, n/a, Spero Therapeutics (Employee)Spero Therapeutics (Employee, Shareholder) Susannah M. Walpole, PhD, Spero Therapeutics, Inc. (Employee) Hanna Kwak, n/a, Spero Therapeutics (Employee) Anne-Marie Phelan, n/a, Spero Therapeutics (Employee)Spero Therapeutics (Employee, Shareholder) Gary E. Moore, BS/MS, Spero Therapeutics (Consultant) Akash Jain, PhD, Spero Therapeutics (Employee) Tim Keutzer, BA, Spero Therapeutics, Inc (Employee) Aaron Dane, MSc, Da Volterra (Consultant)Spero theraputics (Consultant) Aaron Dane, MSc, Spero theraputics (Consultant) David Melnick, MD, Spero Therapeutics (Employee)Spero Therapeutics (Employee) Angela K. Talley, MD, Spero Therapeutics (Employee, Shareholder)